The emerging roles of Shank3 in cardiac function and dysfunction - Kim, Yoonhee; Ko, Tae Hee; Jin, Chunmei; Zhang, Yinhua; Kang, Hyae Rim; Ma, Ruiying; Li, Huiling; Choi, Jong-Il; Han, Kihoon (Frontiers in Cell and Developmental Biology, 2023)
Shank3 is a member of the Shank family proteins (Shank1–3), which are abundantly present in the postsynaptic density (PSD) of neuronal excitatory synapses. As a core scaffold in the PSD, Shank3 plays a critical role in organizing the macromolecular complex, ensuring proper synaptic development and function. Clinically, various mutations of the SHANK3 gene are causally associated with brain disorders such as autism spectrum disorders and schizophrenia. However, recent in vitro and in vivo functional studies and expression profiling in various tissues and cell types suggest that Shank3 also plays a role in cardiac function and dysfunction. For example, Shank3 interacts with phospholipase Cβ1b (PLCβ1b) in cardiomyocytes, regulating its localization to the sarcolemma and its role in mediating Gq-induced signaling. In addition, changes in cardiac morphology and function associated with myocardial infarction and aging have been investigated in a few Shank3 mutant mouse models. This review highlights these results and potential underlying mechanisms, and predicts additional molecular functions of Shank3 based on its protein interactors in the PSD, which are also highly expressed and function in the heart. Finally, we provide perspectives and possible directions for future studies to better understand the roles of Shank3 in the heart.